Design and Processing of Communication and Navigation Integrated Signal Based on LEO Satellite - Binghong LIU; Yafei ZHAO; Mugen PENG; Xiangtian ZHAO; Huiqi FENG (天地一体化信息网络)
The integration of communication and navigation is an important direction in modern satellite communication and navigation fields.The advancement of low earth orbit (LEO) mega-constellations provides the abundant load, link and terminal resources, as well as the powerful communication coverage and information transmission capabilities.Moreover, together with the fast-changing geometric configuration and strong power, the LEO satellites can complement, backup, and enhance the existing navigation systems to provide communication and navigation services with broader coverage, higher precision and reliability.In the LEO satellite-enabled communication and navigation-integrated system, the design of the transmitted signals and the processing of the received signals are crucial for achieving efficient communication and high-precision navigation.To this end, the evolution process of the communication and navigation fusion was first outlined.Then, it focused on the design of transmitting signals and the processing of receiving signals, the relevant schemes included the layout of the frame structure and the receiver were emphasized, respectively.Finally, the challenges and potential solutions that lie ahead in the future were explored.